2021
DOI: 10.1007/s00216-021-03367-8
|View full text |Cite
|
Sign up to set email alerts
|

Peptide array–based interactomics

Abstract: The analysis of protein-protein interactions (PPIs) is essential for the understanding of cellular signaling. Besides probing PPIs with immunoprecipitation-based techniques, peptide pull-downs are an alternative tool specifically useful to study interactome changes induced by post-translational modifications. Peptides for pull-downs can be chemically synthesized and thus offer the possibility to include amino acid exchanges and post-translational modifications (PTMs) in the pull-down reaction. The combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Hence, all the interactors must be confirmed using other methods. 6 In previous studies, proximity ligations, co-immunoprecipitations, and Bio-ID assays successfully confirmed several interaction partners discovered by PrISMa. 3 , 5 …”
Section: Limitationsmentioning
confidence: 56%
See 3 more Smart Citations
“…Hence, all the interactors must be confirmed using other methods. 6 In previous studies, proximity ligations, co-immunoprecipitations, and Bio-ID assays successfully confirmed several interaction partners discovered by PrISMa. 3 , 5 …”
Section: Limitationsmentioning
confidence: 56%
“… 1 , 2 , 3 , 4 , 5 This protocol describes the PrISMa approach as a screening method to target interactions mediated by short linear motifs (SLiMs) in high-throughput. 5 , 6 Since the peptide matrix is chemically synthesized, it allows the inclusion of modified amino acids, like amino acids carrying post-translational modifications or the inclusion of amino acid exchanges caused by mutations.…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptide arrays typically consist of a series of short peptides, each representing a potential epitope of the antigen of interest, and helps to recognize binding sites between proteins [ 12 , 13 , 14 , 15 ]. By incubating the peptide array with sera or cells from an individual with a known immune response to the antigen, it is possible to identify the specific peptides that are recognized by the immune system.…”
Section: Resultsmentioning
confidence: 99%